The applicability of a validated team-based learning student assessment instrument to assess United Kingdom pharmacy students’ attitude toward team-based learning - Leanne Marie Nation; Simon Tweddell; Paul Rutter (Journal of Educational Evaluation for Health Professions, 2016)
Purpose It aimed at testing the validity and reliability of a validated team-based learning student assessment instrument (TBL-SAI) to assess United Kingdom pharmacy students’ attitude toward TBL. Methods TBL-SAI, consisting of 33 items, was administered to undergraduate pharmacy students from two schools of pharmacy each at University of Wolverhampton and University of Bradford were conducted on the data, along with comparison between the two schools. Results Students’ response rate was 80.0% (138/173) in completion of the instrument. Overall, the instrument demonstrated validity and reliability when used with pharmacy students. Sub-analysis between schools of pharmacy did, however, show that four items from Wolverhampton data, had factor loadings of less than 0.40. No item in the Bradford data had factor loadings less than 0.40. Cronbach’s alpha score was reliable at 0.897 for the total instrument: Wolverhampton, 0.793 and Bradford, 0.902. Students showed preference to TBL, with Bradford’s scores being statistically higher (P<0.005). Conclusion This validated instrument has demonstrated reliability and validity when used with pharmacy students. Furthermore students at both schools preferred TBL compared to traditional teaching.